Character education facing the VUCA era through the PJBL model in penjas subjects - Suharti, Suharti; Darmawan, Agung Dwi; Harwanto, Harwanto; gunawan, Wawan; wiyarno, Yoso (Jurnal Maenpo : Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi, 2024)
The aim of this research is to find out : (1) differences Character Education for PENJAS Subjects between the use of Project-Based Learning and conventional methods for Character Education for PENJAS Subjects, (2) differences High interest in learning and low interest in learning in the Character Education of PENJAS Subjects , and (3) the interaction between the learning model and Interest in learning in the Character Education of PENJAS Subjects , in this case Interest as a moderator variable really supports the strong relationship between the independent variable and the dependent variable . This experimental research was carried out using a 2x2 factorial design. The subjects in this research were class VIII students consisting of four classes with 110 group B students. The subjects that were the focus of the experiment were taken at random, namely group B. This research hypothesis was tested using the Analysis of Variant (Anova) statistical test. The calculation results show that: Based on the results of hypothesis testing and discussion, it can be concluded as follows: (1) There is a difference in the influence of using Project-Based Learning and conventional methods on Character Education in PENJAS Subjects , namely that students who use Project-Based Learning are better Subjects PENJAS than students who use conventional methods, (2) There is a difference in the influence of high interest in learning and low interest in learning on character education in PENJAS subjects , namely students with high interest in learning are better in PENJAS subjects than students with low interest in learning, and (3 ) There is an interaction effect between the learning model and interest in learning on the character education of the PENJAS subject , in this case interest as a moderator variable really supports the strong relationship between the independent variable and the dependent variable. The effect of using project-based learning with high interest can improve PENJAS subjects